2017
DOI: 10.1371/journal.pgen.1006786
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent electrical and morphological remodeling of the Drosophila heart caused by hERG/seizure mutations

Abstract: Understanding the cellular-molecular substrates of heart disease is key to the development of cardiac specific therapies and to the prevention of off-target effects by non-cardiac targeted drugs. One of the primary targets for therapeutic intervention has been the human ether a go-go (hERG) K+ channel that, together with the KCNQ channel, controls the rate and efficiency of repolarization in human myocardial cells. Neither of these channels plays a major role in adult mouse heart function; however, we show her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 83 publications
2
14
1
Order By: Relevance
“…However, we were also surprised to find that, although not as striking as in the neuronal knockdown, the organismal response to heat stress also depends on the activity of sei in non-neuronal glia (Fig 3C and 3D). In contrast, although a previous study has indicated that sei activity is important for heart physiology [69], we found that sei knockdown in the heart or body muscles has no effect on seizure susceptibility (Fig 3E–3H). Together with the strong effect of pan-neuronal sei knockdown on heat-induced seizures, these data suggest that the effects of the sei mutations on seizure susceptibility are independent of sei action in the heart.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, we were also surprised to find that, although not as striking as in the neuronal knockdown, the organismal response to heat stress also depends on the activity of sei in non-neuronal glia (Fig 3C and 3D). In contrast, although a previous study has indicated that sei activity is important for heart physiology [69], we found that sei knockdown in the heart or body muscles has no effect on seizure susceptibility (Fig 3E–3H). Together with the strong effect of pan-neuronal sei knockdown on heat-induced seizures, these data suggest that the effects of the sei mutations on seizure susceptibility are independent of sei action in the heart.…”
Section: Resultscontrasting
confidence: 99%
“…Previous studies by us and others have indicated that the sei gene is expressed in diverse neuronal and non-neuronal cell types, including cardiac and muscle cells [43, 68, 69], and that mutations in sei increase the overall organismal sensitivity to acute heat stress, resulting in shorter latency to heat-induced seizures and paralysis [3335]. Yet, whether this organismal phenotype is driven by the action of sei in all cell types that express it was unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Muscle tissue defects and electrical activity have been linked in mouse and humans (Chinchilla and Franco, 2006). Moreover, mutations in seizure [the Drosophila homolog of the human K + channel gene hERG (also known as KCNH2), which is important in cardiac repolarization] not only cause bradycardia and arrhythmia, but also structural defects such as myofibrillar disorganization (Ocorr et al, 2017). Silencing of CNOT2/Not2, CNOT4/Not4 and CNOT6/6L/twin subunits led overall to similar, albeit weaker, phenotypes limited to increased diastolic and systolic diameters.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of CNOT2/Not2, CNOT4/Not4 and CNOT6/6L/twin subunits led overall to similar, albeit weaker, phenotypes limited to increased diastolic and systolic diameters. Importantly, the role of CNOT subunits in the action potential repolarization phase was demonstrated not only in the Drosophila heart model (Ocorr et al, 2017), but also in humans (Tse et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The human K + channel ether-à-go-go gene (hERG) might also be interested by age-dependent mutations causing rhythm instabilities, as well as disorganization of the structure of the sarcomeric structure and myofibrillary proteins, as evidenced in a mouse model of a mutated hERG homolog [ 51 ].…”
Section: Positive and Negative Effects Of Senescence On Cardiovascmentioning
confidence: 99%